2015
DOI: 10.1186/s12872-015-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacity and heart rate response: associations with nocturnal hypertension

Abstract: BackgroundAbsences of normative, 10–20 % declines in blood pressure (BP) at night, termed nocturnal non-dipping, are linked to increased cardiovascular mortality risks. Current literature has linked these absences to psychological states, hormonal imbalance, and disorders involving hyper-arousal. This study focuses on evaluating associations between nocturnal non-dipping and indices of functional cardiac capacity and fitness.MethodsThe current study was a cross-sectional evaluation of the associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Data regarding the association between circadian BP rhythm and functional capacity are scarce. Ritvo et al showed no difference in exercise capacity between dippers and non‐dippers. However, the authors showed significant correlation between exercise capacity and dipping BP pattern …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Data regarding the association between circadian BP rhythm and functional capacity are scarce. Ritvo et al showed no difference in exercise capacity between dippers and non‐dippers. However, the authors showed significant correlation between exercise capacity and dipping BP pattern …”
Section: Introductionmentioning
confidence: 95%
“…Ritvo et al showed no difference in exercise capacity between dippers and non‐dippers. However, the authors showed significant correlation between exercise capacity and dipping BP pattern …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although DBP usually remains unchanged or shows only little rise during exercise testing in healthy individuals, 25 a significant increase of DBP at peak exercise comes parallel with advancing age, 26,27 related to impaired capacity in exercise-induced vasodilation in older subjects. Previous studies 27,28 have illustrated HR response to exercise as a predictor of future HTN. Although the underlying mechanisms are not clear, impaired baroreflex sensitivity and autonomic dysfunction have been proposed as possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms are not clear, impaired baroreflex sensitivity and autonomic dysfunction have been proposed as possible mechanisms. 2729…”
Section: Discussionmentioning
confidence: 99%